1992
DOI: 10.1007/bf02493439
|View full text |Cite
|
Sign up to set email alerts
|

Can protein-calorie malnutrition cause dysphagia?

Abstract: Nutrient deprivation has previously been shown to cause alterations in muscle and nerve function. Although an effect has never been studied in the neuromusculature of deglutition, the authors argue that an effect is likely. The proposed result is an increase in swallowing impairment in dysphagic individuals and associated risk of aspiration. Research studying the relationship between malnutrition and dysphagia is needed to verify clinical significance. Until controlled studies are completed, the authors sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 99 publications
(116 reference statements)
0
48
0
Order By: Relevance
“…A hypermetabolic disease is characterized by an elevation in basal metabolic rate (BMR) or resting energy expenditure (REE) due to the complications of an associated disease or acute trauma. In addition, Veldee and Peth [40] postulated that the multiplicity of muscles involved in deglutition have a moderate to high percentage of type II fibers present because successful swallowing is characterized by synchronized, rapid contractions requiring speed and short bursts of activity. Type II (fast twitch) muscle fibers are affected by PEM to a much greater extent than are type I fibers (slow twitch) [34,38,39,42].…”
Section: Effects Of Pem On the Dysphagicmentioning
confidence: 99%
See 1 more Smart Citation
“…A hypermetabolic disease is characterized by an elevation in basal metabolic rate (BMR) or resting energy expenditure (REE) due to the complications of an associated disease or acute trauma. In addition, Veldee and Peth [40] postulated that the multiplicity of muscles involved in deglutition have a moderate to high percentage of type II fibers present because successful swallowing is characterized by synchronized, rapid contractions requiring speed and short bursts of activity. Type II (fast twitch) muscle fibers are affected by PEM to a much greater extent than are type I fibers (slow twitch) [34,38,39,42].…”
Section: Effects Of Pem On the Dysphagicmentioning
confidence: 99%
“…Type II (fast twitch) muscle fibers are affected by PEM to a much greater extent than are type I fibers (slow twitch) [34,38,39,42]. Therefore, deglutitive muscles may be among the first to atrophy because of reduced food intake, compromising the integrity of the swallow, further decreasing intakes and increasing the risk of aspiration [40].…”
Section: Effects Of Pem On the Dysphagicmentioning
confidence: 99%
“…Prolonged conditions with protein-energy malnutrition (PEM) can deprive immune functions and increase morbidity from infectious diseases and mortality [6][7][8]. It has also been suggested that PEM may alter muscle and nerve function and thereby increase swallowing impairment [9]. Different therapeutic strategies have been introduced to improve swallowing impairment [10].…”
mentioning
confidence: 99%
“…Although our patient was not reported to have a history of cerebrovascular accident, a brainstem event presenting primarily as dysphagia cannot be ruled out [10]. Veldee et al [11] report nutrient deprivation to cause alterations in muscle and nerve function and although an eect has not been studied in the neuromusculature of deglutition, the authors argue that an eect is likely [11].…”
Section: Discussionmentioning
confidence: 99%